The Importance of Work Motivation for Employee Productivity - Arvina Nur Aeni; Nur Haifa; Rifa’ah Alya Putrianti; Rika Refani Az-zahra (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to summarize and describe the importance of work motivation in enhancing employee performance. The method employed in this article is a literature review, involving the collection of relevant sources such as books, scholarly journals, and previous research articles. The findings indicate that work motivation serves as a key factor in boosting employee productivity, discipline, sense of responsibility, and work quality. The article presents several effective strategies for enhancing work motivation, including providing opportunities for career development and growth, ensuring role clarity, creating a conducive work environment, and involving employees in decision-making processes. Furthermore, tailoring motivational approaches to individual employee needs is crucial for fostering work enthusiasm. Strong motivation is key to achieving optimal performance in every employee. Leaders play a vital role in creating a work environment that boosts employee morale by recognizing achievements, offering positive work challenges, and aligning organizational goals with individual objectives. Consequently, employees are expected to become more motivated and develop greater self-confidence, loyalty, and commitment to the organization, leading to a significant improvement in their performance.